1958
DOI: 10.1021/jo01100a010
|View full text |Cite
|
Sign up to set email alerts
|

Some Reactions of Methanesulfinyl Chloride1

Abstract: SOME REACTIONS OF METHANESULFINYL CHLORIDE 805 160°/16 mm.; n2¿ 1.6112. On redistillation, through a 30cm. Fenske ring-packed column at a reflux ratio of 1:10, the product obtained possessed the following constants: b.p. 135-137°/4 mm.; n2Ds 1.6110; 1.1040.3-Isopropylidene-3-pentenenitrile9 (VIII). Acetone was condensed with 3-pentenenitrile in the same manner as described above for benzaldehyde. The product was distilled through a 76-cm. Nester spinning band column at a reflux ratio of 1:10. The liquid produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The Friedel–Crafts sulfinylation of aromatic compounds to form diaryl or alkyl aryl sulfoxides is relatively unexplored given that the synthesis of phenyl p -tolyl sulfoxide from benzene and p -toluenesulfinyl chloride was reported in 1926 . More than 30 years later, Douglas et al reported a 26% yield of methyl phenyl sulfoxide by reaction of benzene with methanesulfinyl chloride in the presence of anhydrous aluminum chloride, and Replogle and Maynard described low yields of the corresponding sulfoxides for the direct electrophilic sulfinylation of the azulene ring with alkane or arenesulfinyl chlorides. Olah and Nishimura have reported the high selectivity of the aluminum chloride catalyzed arenesulfinylation of benzene and polymethylbenzenes with substituted benzenesulfinyl chlorides in nitromethane solution, whereas Chasar and Pratt prepared a number of 2- and 4-hydroxydiaryl sulfoxides by the direct arenesulfinylation of substituted phenols in the presence of anhydrous aluminum chloride.…”
Section: Introductionmentioning
confidence: 99%
“…The Friedel–Crafts sulfinylation of aromatic compounds to form diaryl or alkyl aryl sulfoxides is relatively unexplored given that the synthesis of phenyl p -tolyl sulfoxide from benzene and p -toluenesulfinyl chloride was reported in 1926 . More than 30 years later, Douglas et al reported a 26% yield of methyl phenyl sulfoxide by reaction of benzene with methanesulfinyl chloride in the presence of anhydrous aluminum chloride, and Replogle and Maynard described low yields of the corresponding sulfoxides for the direct electrophilic sulfinylation of the azulene ring with alkane or arenesulfinyl chlorides. Olah and Nishimura have reported the high selectivity of the aluminum chloride catalyzed arenesulfinylation of benzene and polymethylbenzenes with substituted benzenesulfinyl chlorides in nitromethane solution, whereas Chasar and Pratt prepared a number of 2- and 4-hydroxydiaryl sulfoxides by the direct arenesulfinylation of substituted phenols in the presence of anhydrous aluminum chloride.…”
Section: Introductionmentioning
confidence: 99%
“…The above strategy was utilized in syntheses of not only "small molecules" but also polymeric systems (5) starting from polysulfoxides (6) as substrates (Scheme 2). The first illustration of this new methodology was synthesis of dibenzothiophene (7) and dibenzo[b,b']thieno[2,3-f :5,4-f ']bis [1]benzothiophene (DBTBT, 8) reported by Sirringhaus and coworkers. The syntheses proceeded via the acid-induced intramolecular cyclization reaction of arenes containing methyl sulfoxide groups, i.e., methylsulfinylbiphenyl (9) and 3,7-bis(methylsulfinylo phenyl)dibenzothiophene.…”
Section: Cyclisation Of Sulfur Derivativesmentioning
confidence: 99%
“…The first literature report concerning intermolecular Friedel-Crafts sulfinylation of aromatic compounds, starting from diaryl or alkyl aryl sulfoxides, was published in 1926 by Farah and coworkers [ 6 ]. After 30 years, Douglas et al reported the synthesis of methyl phenyl sulfoxide from benzene and methanesulfinyl chloride in the presence of AlCl 3 [ 7 ]. Also, Gupta published the synthesis of aromatic N , N -dialkylsulfonamides via the reaction of dialkylsulfamyl chlorides with aromatic hydrocarbons in the presence of AlCl 3 [ 8 ].…”
Section: Cyclisation Of Sulfur Derivativesmentioning
confidence: 99%
“…Other important fragments Yn/e were observed at 182 (26, $-H~NSC-CGH~-CH~-S) ; 150(37, P-HzNSC-C6H4--CHs) ; 148 (13, NC-C6H4-CH2-S) ; 122 (26, CsH4CH2-S) ; 102 (10, NC-CsH4) ; 90 (47, C6H4-CH2) ; 60 (16,H2NSC).…”
Section: A Convenient Alkyl Cycloalkyl and Aralkyl Disulfides Synthementioning
confidence: 99%